In silico analysis and functional characterization of a leucine-rich repeat protein of Leptospira interrogans - João P. Gaspar; Maria B. Takahashi; Aline F. Teixeira; Ana L.T.O. Nascimento (Elsevier, 2024)
Pathogenic spirochetes of the genus Leptospira are the causative agent of leptospirosis, a widely disseminated zoonosis that affects humans and animals. The ability of leptospires to quickly cross host barriers causing infection is not yet fully understood. Thus, understanding the mechanisms of pathogenicity is important to combat leptospiral infection. Outer membrane proteins are interesting targets to study as they are able to interact with host molecules. Proteins containing leucine-rich repeat (LRR) domains are characterized by the presence of multiple regions containing leucine residues and they have putative functions related to host-pathogen interactions. Hence, the present study aimed to clone and express the recombinant protein encoded by the LIC11098 gene, an LRR protein of L. interrogans serovar Copenhageni. In silico analyses predicted that the target protein is conserved among pathogenic strains of Leptospira, having a signal peptide and multiple LRR domains. The DNA sequence encoding the LRR protein was cloned in frame into the pAE vector, expressed without mutations in Escherichia coli and purified by His-tag chromatography. Circular dichroism (CD) spectrum showed that the recombinant protein was predominantly composed of β-sheets. A dose-dependent interaction was observed with cellular and plasma fibronectins, laminin and the complement system component C9, suggesting a possible role of the protein encoded by LIC11098 gene at the initial stages of infection.